Confined synthesis of 2D nanostructured materials toward electrocatalysis - Li, Zhenhua (2020)
2D nanostructured materials have shown great application prospects in energy conversion, owing to their unique structural features and fascinating physicochemical properties. Developing efficient approaches for the synthesis of well‐defined 2D nanostructured materials with controllable composition and morphology is critical. The emerging concept, confined synthesis, has been regarded as a promising strategy to design and synthesize novel 2D nanostructured materials. This review mainly summarizes the recent advances in confined synthesis of 2D nanostructured materials by using layered materials as host matrices (also denoted as “nanoreactors”). By virtue of the space‐ and surface‐confinement effects of these layered hosts, various well‐organized 2D nanostructured materials, including 2D metals, 2D metal compounds, 2D carbon materials, 2D polymers, 2D metal‐organic frameworks (MOFs) and covalent‐organic frameworks (COFs), as well as 2D carbon nitrides are successfully synthesized. The wide employment of these 2D materials in electrocatalytic applications (e.g., electrochemical oxygen/hydrogen evolution reactions, small molecule oxidation, and oxygen reduction reaction) is presented and discussed. In the final section, challenges and prospects in 2D confined synthesis from the viewpoint of designing new materials and exploring practical applications are commented, which would push this fast‐evolving field a step further toward greater success in both fundamental studies and ultimate industrialization.